'It's like the bad guy in a movie who just doesn't die': a qualitative exploration of young people's adaptation to eczema and implications for self‐care. (1st January 2020) - Ghio, D.; Muller, I.; Greenwell, K.; Roberts, A.; McNiven, A.; Langan, S.M.; Santer, M.
Summary: Background: Eczema is a common childhood inflammatory skin condition, affecting more than one in five children. A popular perception is that children 'outgrow eczema', although epidemiological studies have shown that, for many, eczema follows a lifelong episodic course. Objectives: To explore the perceptions of young people about the nature of their eczema and how these perceptions relate to their self‐care and adapting to living with eczema. Methods: This is a secondary inductive thematic analysis of interviews conducted for Healthtalk.org. In total 23 interviews with young people with eczema were included. Of the 23 participants, 17 were female and six male, ranging from 17 to 25 years old. Results: Participants generally experienced eczema as an episodic long‐term condition and reported a mismatch between information received about eczema and their experiences. The experience of eczema as long term and episodic had implications for self‐care, challenging the process of identifying triggers of eczema flare‐ups and evaluating the success of treatment regimens. Participants' experiences of eczema over time also had implications for adaptation and finding a balance between accepting eczema as long term and hoping it would go away. This linked to a gradual shift in treatment expectations from 'cure' to 'control' of eczema. Conclusions: For young people who continue to experience eczema beyond childhood, a greater focus on self‐care for a long‐term condition may be helpful. Greater awareness of the impact of early messages around 'growing out of' eczema and provision of high‐quality information may help patients to manage expectations and support adaptation to treatment regimens. What's already known about this topic? There is a common perception that people 'grow out of' eczema, but for many people eczema follows a lifelong episodic course. Qualitative work has shown that parents can find that being told their child will grow out of eczema is dismissive, and that they have difficulty with messages about 'control not cure' of eczema. It is unclear how young people perceive their eczema and the implications of this perception for their adaptation and self‐care. What does this study add? The message that many people 'grow out of' eczema has a potentially detrimental effect for young people where the condition persists. This has implications for young people's perceptions of their eczema, their learning to self‐care and how they adapt to living with eczema and eczema treatments. What are the clinical implications of this work? Clinicians need to promote awareness among young people that eczema is a long‐term episodic condition in order to engage them with effective self‐care. Young people transitioning to self‐care need evidence‐based information that is specific and relatable to them.